A novel green synthesis of ZrO nanoparticles as a corrosion inhibitor on ASTM-415 carbon steel in 0.5 M H2SO4 - Sivakumar Sivalingam; Megala Rajendran; Jayagopi Gayathri; S. Anu; Jyoti Kavirajwar; Mihir Ghosh (Results in Chemistry)
ZrO-SyzygiumCuminicomposite was evaluated for its ability to inhibit corrosion on ASTM-415 carbon steel in 0.5 M H2SO4 by means of corrosion characterization methods, including phase angle/degree, frequency, potentiodynamic polarization (PDP), electrochemical impedance spectroscopy (EIS), and gravimetric assessment. As the concentration of ZrO-SyzygiumCumini composite increased, the results demonstrated that the dynamic corroding area were resist completely., resulting in the creation of a barrier layer on the working electrode surface. Furthermore, even in extremely corrosive settings, the presence of ZrO-SyzygiumCumini complex inhibitor decreased the rate of corrosion of carbon steel. Recently synthesized ZrO-SyzygiumCumini compound was subjected to FT-IR, XRD, and SEM-EDAX spectroscopic analysis.